Results of a phase 1/2 study of sacituzumab tirumotecan in patients with unresectable locally advanced or metastatic solid tumors refractory to standard therapies - Quchang Ouyang; Jordi Rodon; Yan Liang; Xinhong Wu; Qun Li; Lihua Song; Min Yan; Zhongsheng Tong; YunPeng Liu; Zev A. Wainberg; Ying Wang; Cuizhi Geng; et al. (Journal of Hematology & Oncology)
Abstract Background Sacituzumab tirumotecan (sac-TMT) is an antibody–drug conjugate composed of an anti-TROP2 monoclonal antibody coupled to a cytotoxic belotecan-derived topoisomerase I inhibitor (KL610023) via a novel linker. We report results from the phase 1 dose-escalation cohorts in advanced solid tumors and phase 2 expansion cohorts for metastatic triple-negative breast cancer (TNBC) from the first-in-human MK-2870-001 (KL264-01) study (NCT04152499). Methods Patients had unresectable locally advanced/metastatic solid tumors refractory to standard therapies. In the phase 1 dose-escalation cohorts, patients had unresectable locally advanced/metastatic solid tumors refractory to standard therapies. Sac-TMT was administered by intravenous administration every 2 weeks at 2 to 12 mg/kg. In phase 2, patients with TNBC and HR+/HER2− breast cancer received sac-TMT per recommended doses for expansion (RDEs) identified in phase 1. Primary objectives were determining maximum tolerated dose (MTD) of sac-TMT and establishing RDEs (phase 1) and determining ORR per RECIST v1.1 by investigator assessment (phase 2). Adverse events were assessed per NCI-CTCAE version 5.0. Results Thirty patients were enrolled in phase 1 and received sac-TMT 2 mg/kg (n = 4), 4 mg/kg (n = 7), 5 mg/kg (n = 7), 5.5 mg/kg (n = 5), and 6 mg/kg (n = 7). Five patients had dose-limiting toxicities: grade 3 stomatitis at 4, 5.5, and 6 mg/kg; grade 3 rash at 5 mg/kg; and grade 3 urticaria at 6 mg/kg. MTD was 5.5 mg/kg and RDEs were 4 and 5 mg/kg. In the phase 2 dose expansion, ORR (95% CI) was 34.8% (16.4%, 57.3%) in the 4-mg/kg group (n = 23) and 38.9% (23.1%, 56.5%) in the 5-mg/kg group (n = 36) for TNBC. ORR (95% CI) was 31.7% (18.1%, 48.1%) for HR+/HER2− breast cancer (n = 41). Conclusions Sac-TMT demonstrated manageable safety profile in patients with unresectable locally advanced/metastatic solid tumors and promising antitumor activity in metastatic TNBC and HR+/HER2 − breast cancer. Sac-TMT is being investigated in phase 3 studies. Trial registration ClinicalTrials.gov, NCT04152499.